Infectious keratitis: a molecular and clinical study - Otri, Ahmad Muneer (2013)
Infectious keratitis is a sight threatening disease which can cause permanent visual loss if not diagnosed and treated at an early stage. It can be caused by different types of microbes which are either commensals or transferred from the environment. To fight against these threats, the ocular surface (OS) has developed innate and adaptive immune mechanisms. Antimicrobial peptides (AMPs) are natural effectors on the OS with actions that range from microbicidal effects to cell signalling. Human beta defensin (hBD) 1-3 and 9, Liver expressed antimicrobial peptide (LEAP) 1 and 2, human cathelicidin (LL37), ribonuclease7 (RNase7) are the main AMPs on the OS.